Mammographic and ultrasonographic features of invasive lobular carcinoma: A review of 16 patients - M. Muttarak (2018)
Objectives: To review the mammographic and ultrasonographic findings of invasive lobular carcinoma (ILC), determine the role of ultrasonography (US) in the detection of ILC, and determine if ILC is frequently missed on mammography. Materials and methods: Approval by Institutional Review Board was granted. Between January 2000 and July 2008, medical records and pathological diagnosis of 1,146 invasive breast carcinomas at the authors' institution were retrospectively reviewed. Only patients with pathologically-proven pure ILC were included. The initial mammographic reports were analysed to determine the true-positive and false-negative rates for the detection of cancer. Results: There were 37 patients diagnosed as pure ILC which accounted for 3% of all invasive breast carcinoma. Of the 37 patients, 16 had imaging studies and constituted the material of this study. The patients ranged in age from 45-76 years (mean age, 56.43 years). Of the 16 patients, one was asymptomatic, one presented with bleeding tendency and was found to have factor VIII abnormality (mammography was performed to search for primary breast carcinoma), one presented with left breast enlargement with left axillary mass, one presented with right axillary mass, and 12 presented with palpable breast mass(es). Mammographic breast density was extremely dense in five, heterogeneously dense in eight, scattered fibroglandular density in three, and fatty in one. Four patients had bilateral breast carcinoma and one had multicentricity. The carcinoma was correctly detected on initial mammographic evaluation in 15 patients (93.75%). The most common mammographic finding was architectural distortion (8/16 = 50%). The most common US finding was irregular hypoechoic mass (15/18 = 83.3%). There were 18 tumours in 16 patients. Mammography detected 16 tumours but US detected 18 tumours. US was not better than mammography in the detection of tumours but was helpful in the detection of multicentricity and guide biopsy. Conclusion: The most common mammographic feature of ILC was architectural distortion and the most common US feature of ILC was irregular or ill-defined hypoechoic mass with acoustic shadowing. These findings were similar to other studies. The rate of missed diagnosis was not high but this is likely because most of our patients were symptomatic. US was not helpful to improve detection of ILC but was helpful to confirm the suspicious abnormalities on mammograms, detect multicentricity and guide biopsy. © 2010 Biomedical Imaging and Intervention Journal.